Employee institutional trust as an antecedent of diverse dimensions of organisational commitment - Lewicka, Dagmara (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The purpose of this study is to investigate the impact of the level of institutional trust upon employee commitment. Four types of organisational trust were taken into consideration: affective, normative, benefit-based and fear-based continuance. The influence of trust propensity upon the level of institutional trust was also tested. The survey was conducted in Poland on 444 randomly selected employees. Structural equation models were estimated confirming hypothesized relationships and explaining the substantial amount of variance of commitment measures. The research results allowed for verifying the model presenting relationships between institutional trust and commitment. The model indicates a significant impact of the institutional trust onto different types of organisational commitments, i.e. affective commitment, normative commitment, continuance benefit-based and fear-based commitment. In addition, the impact of trust propensity onto the degree of institutional trust of respondents was confirmed. The results of the study show that institutional trust in organisations must be developed in full awareness of its implications as the degree of the trust severely influences all types of organisational commitment, for this reason they should inspire management to actions aimed at growing the institutional trust. This study clearly demonstrates the importance of institutional trust as an organisational commitment-building factor. Up till now research was focused on the search for a relationship between the level of interpersonal trust and the level of organisational commitment, with regretfully little attention paid to institutional trust. The study confirmed the impact that institutional trust has on all four different types of organisational commitment, including two aspects of continuance commitment: benefit-based commitment and fear-based commitment, developed by the author
Argumenta Oeconomica, 2020, Nr 1 (44), s. 321-340